KORFBALL AS A INTEGRATION OF GENDERS TOOL: A PROPOSAL OF WORK IN FORMAL SPACES OF TEACHING. (Fiep Bulletin - online, 2014)
This research has as goal to present a work proposal aiming the gender integration inside formal education spaces (schools), using an old sport, with more than one hundred years of history and very known in Europe and Asia, but not very known by the majority of the Brazilian teachers, although some journalistic substances in media: Korfball. After a soon introduction on the importance of korfball as a powerful tool of work in schools is given, the concepts of gender and the basic rules for the understanding had been seen of how korfball will be able to act following this proposal. Contextualization with the current physical education had been made, being cited examples of how it gives the process of construction of this dichotomy that exists between men and women in elapsing of their school and social life and how to make with that this same dichotomy wastes and, of this form, begin a constant process of reflection about the possibility of construction of new concepts, based on a perspective of cultural dynamic. Finally, the work proposal was built placing korfball as a form of intervention in the spaces of work in the schools, as an anthropologic-cultural thought and based on the cultural concepts of gender and studies that they corroborate for the practical one of the sport for such objective.
Keywords: korfball; gender; school physical education